2003
DOI: 10.1074/jbc.m213071200
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor-dependent Repression of Matrix Metalloproteinase-9 Expression in Macrophages

Abstract: Matrix metalloproteinases (MMPs) are zinc endopeptidases that degrade extracellular matrix (ECM) components during normal and pathogenic tissue remodeling. Inappropriate expression of these enzymes contributes to the development of vascular pathology, including atherosclerosis. MMP-9 is expressed in its active form in atherosclerotic lesions and is believed to play an important role in vascular remodeling, smooth muscle cell migration, and plaque instability. We demonstrate here that the liver X receptors (LXR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
257
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(271 citation statements)
references
References 47 publications
10
257
2
2
Order By: Relevance
“…The expression and secretion of ECM-modifying MMPs is an important determinant of tumor invasion. MMP expression is regulated at the transcriptional level and the MMP promoters contain NF-kB (Chen et al, 2009;Oh et al, 2009), which have been shown to regulate MMP-12 promoter activity (Castrillo et al, 2003;Sampath et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The expression and secretion of ECM-modifying MMPs is an important determinant of tumor invasion. MMP expression is regulated at the transcriptional level and the MMP promoters contain NF-kB (Chen et al, 2009;Oh et al, 2009), which have been shown to regulate MMP-12 promoter activity (Castrillo et al, 2003;Sampath et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increase in PTPN1 production and activity induced by TNFα was completely prevented by T0901317. The mechanisms of this inhibitory action are unknown, and so far no NR1HR response elements have being identified on the Ptpn1 promoter, although the induction by cytokines of the expression of other genes, such as that encoding matrix metalloproteinase-9 in macrophages, was repressed by NR1HR activation [44]. One group has identified on the Ptpn1 promoter two regulatory elements that recognise Y box-binding protein-1 and Sp family transcription factors, both of which are required for optimal promoter activity [45].…”
Section: Discussionmentioning
confidence: 99%
“…32,48,49 In animal models of atherosclerosis, such as apolipoprotein E-deficient (apoE Ϫ/Ϫ ) and LDL receptor-deficient (LDLR Ϫ/Ϫ ) mice, we found that LXR ligand treatment reduced the development of atherosclerosis. 34 Moreover, recent studies revealed that the LXR signaling pathway links innate immunity to macrophage cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition LXRs also play a role in innate immunity and regulate inflammatory gene expression in macrophages. [31][32][33] Indeed, synthetic LXR agonists have been shown to both delay the development of atherosclerosis in genetically prone mouse models and induce regression of preexisting atherosclerotic lesions. 34 -36 In the absence of ligand, heterodimers of LXR and retinoid X receptor, in complex with corepressors such as nuclear receptor corepressor (NCoR) and the related factor SMRT (Silencing Mediator of Retinoic acid and Thyroid hormone receptors), are bound to LXR-responsive elements and inhibit target gene transcription.…”
mentioning
confidence: 99%